The anti-venom potential of Andrographis paniculata (Burm.f.) Nees roots and its constituent skullcapflavone I - Tan, Maria Carmen S. (Animo Repository, 2019)
The anti-venom activity of Andrographis paniculata (Burm.f.) Nees roots (APR) dichloromethane crude extracts and a promising APR constituent, skullcapflavone I (SKI) was investigated by monitoring the inhibition of secretory phospholipase A 2 (sPLA 2) of Naja philippinensis Taylor venom (NPV) crystallized samples. Gas chromatography-mass spectrometry was used for the characterization of extracts, while molecular docking was utilized to understand anti-venom properties. Chromatographic analyses primarily revealed the presence of methoxylated flavones. NPV was found to have sPLA 2 activity (0.0796 ± 0.0018 μmol/minutes/ml) that has been attributed to the poisonous effects. SKI (IC 50 : 51.1 ± 3.5 μg/ml), isolated from APR showed strong inhibitory effect on phospholipase activity compared with dichloromethane extracts of APR (IC 50 : 192.7 ± 10.9 μg/ml) indicating that SKI was the cause of the bioactivity in APR. Molecular docking simulations showed corresponding results with highly negative binding energies (−6.59 to −8.72 kcal/mol) predicted for the binding of SKI to PLA 2 proteins. An important trend found was the presence of free bound Ca 2+ lowered binding energies signifying that Ca 2+ a has role in the binding of the SKI to PLA 2 proteins. The anti-venom property of APR and the pure compound SKI, upon further studies, could be the first line of defense in the medical protocol of snake venom neutralization.